Performance of reverse logistics in electronic commerce: a case study from Lebanon and Syria - Davidavičienė, Vida; Al Majzoub, Mohamad (Transport, 2021)
The technological advancements facilitated the progress of the Business-To-Consumer (B2C) e-commerce business tremendously. B2C e-commerce has several benefits such as saving costs by decreasing the use of resources, increasing profits, and competitive advantage, especially in the pandemic context. However, this opportunity comes with challenges, and one of such is related to a significant number of products that are returned to the vendor or manufacturer. These challenges in the Reverse Logistics’ (RL) in the context of e-commerce become a new phenomenon – Reverse E-Logistics’ (REL), because the product in the e-commerce is physical goods or electronic ones like videos, music, books, etc. This study focuses on identifying the most critical factors that impact REL performance and discusses how REL can affect its performance. The methodology used is mainly a literature review, synthesis, survey methods, and Structural Equation Modelling (SEM). This study is done in Lebanon and Syria with a sample of 412 companies that perform B2C e-commerce and are faced with REL’ . The results showed that out of the ten factors identified during the literature review, eight factors (management, employees, IT and technology, return policy and procedures/guarantee, infrastructure, organizational structure and culture, customer services/satisfaction, and quality management) have a positive correlation with REL performance. Moreover, improved REL performance results increase in companies’ performances. The business research model was created based on performed REL performance in Lebanon and Syria, and this gives new scientific insights and knowledge about REL specificity in developing countries. First published online 21 May 2021